2003
DOI: 10.3171/jns.2003.98.3.0507
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative monitoring of blood flow insufficiency in the anterior choroidal artery during aneurysm surgery

Abstract: The findings of this study suggest that the monitoring method that is introduced here is safe and reliable for detecting intraoperative BFI in the AChA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(83 citation statements)
references
References 24 publications
0
82
0
1
Order By: Relevance
“…5 Shibata et al 10 reported that the use of intraoperative microvascular Doppler sonography (MDS) decreased the incidence of postoperative AchoA syndrome from 16% to 5%. More recently, Suzuki et al 11 reported that intraoperative monitoring of MEPs in 108 patients with ICA aneurysms was reliable for detecting insufficiency of AchoA perfusion intraoperatively. In our study, intraoperative monitoring of MEPs was not routinely used, but intraoperative MDS was used.…”
Section: -5mentioning
confidence: 99%
“…5 Shibata et al 10 reported that the use of intraoperative microvascular Doppler sonography (MDS) decreased the incidence of postoperative AchoA syndrome from 16% to 5%. More recently, Suzuki et al 11 reported that intraoperative monitoring of MEPs in 108 patients with ICA aneurysms was reliable for detecting insufficiency of AchoA perfusion intraoperatively. In our study, intraoperative monitoring of MEPs was not routinely used, but intraoperative MDS was used.…”
Section: -5mentioning
confidence: 99%
“…3,4,7,18,19,34,40,48,60 Intraoperative mapping and monitoring involving CMAPs is a valid modality for reducing iatrogenic morbidity during surgery in and around the central region as well as for intracranial aneurysms. 7,10,11,26,38,39,42,44,[49][50][51][52]62 Two methods are used for intraoperative mapping and monitoring during surgery in and around the insula. The first is the TCES of the motor cortex.…”
mentioning
confidence: 99%
“…Doppler sonography and motor evoked potential monitoring could be used for more reliable confirmation of the patency of the anterior choroidal arteries than visual inspection. 8,10) …”
Section: Discussionmentioning
confidence: 99%